Implementing an online shop website to increase product marketing and sales - Ragil Wahyudi; Wasti Nurgia (JUDIMAS, 2021)
Selling product is a problem faced by business people, especially in this increasingly rapid technological development, especially businesses that are still using conventional methods. Many business people are already using website to market their products or sell their products, this causes businesses that do not use the website to lose competitiveness, especially in the marketing and buying and selling process, such as the Galaxy Ponsel that has not used the website. The purpose of this research is to implement a computerized sales website at the Galaxy and to be able to expand product marketing and sales through the website. In developing this system, the form of research used is a case study using the Design Science Research Method. After being designed, the researcher built a website using the PHP, CSS, Javascript, and MySQL with the help of the Codeigniter Framework. The results of the website design that are made can make transactions as users and as admins can add products and manage orders through the website. The website interface has been successfully created with an attractive appearance and is easy to use. Input Output issued on the website, tested by researchers with white-box testing and the results did not errors.